Endocrine contribution to the sexual dysfunction in patients with advanced chronic kidney disease and the role of hyperprolactinemia - Haitham Elbardisi (14058048) (2021)
In this study, we investigated the prevalence of sexual dysfunction among males with advanced chronic kidney disease and the effect of treating hyperprolactinemia among these patients. In this prospective study, patients were assessed with history, physical examination, hormonal assessment, and two questionnaires, IIEF and AIPE. Patients with hyperprolactinemia received treatment with cabergoline 0.5 mg once per week for 6 months and were re-evaluated. A total of 102 patients were included in this study, 75 (73.53%) were on hemodialysis, 13 (12.75%) on peritoneal dialysis and 14 (13.73%) on medical treatment alone. Ninety (88.24%) patients had premature ejaculation, 85 (83.33%) had anything from mild-to-moderate-to-severe erectile dysfunction. The incidence of hypogonadism and hyperprolactinemia was 34.4%. Patients treated with cabergoline (n = 26) showed a significant increase in LH levels (p = .003) and a significant decrease in prolactin levels (p = .003). Testosterone levels and the incidence of erectile dysfunction or premature ejaculation did not improve significantly. There is a high incidence of sexual dysfunction among patients. Treatment of hyperprolactinemia is effective in correcting prolactin levels, but does not improve erectile dysfunction or premature ejaculation. Therefore, treating hyperprolactinemia is not an overall effective treatment for erectile dysfunction in these patients. Other Information Published in: Andrologia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/and.14135